A Patient-Controlled Analgesia Adaptor to Mitigate Postsurgical Pain for Combat Casualties With Multiple Limb Amputation: A Case Series. Issue 8 (1st August 2016) - Pasquina, Paul F.; Isaacson, Brad M.; Johnson, Elizabeth; Rhoades, Daniel S.; Lindholm, Mark P.; Grindle, Garrett G.; Cooper, Rory A.
ABSTRACT: The use of explosive armaments during Operation Iraqi Freedom, Operation Enduring Freedom, and Operation New Dawn has resulted in a significant number of injured U.S. service members. These weapons often generate substantial extremity trauma requiring multiple surgical procedures to preserve life, limb, and restore function. For those individuals who require multiple surgeries, the use of patient-controlled analgesia (PCA) devices can be an effective way to achieve adequate pain management and promote successful rehabilitation and recovery during inpatient treatment. A subpopulation of patients are unable to independently control a PCA device because of severe multiple limb dysfunction and/or loss. In response to the needs of these patients, our team designed and developed a custom adaptor to assist service members who would otherwise not be able to use a PCA. Patient feedback of the device indicated a positive response, improved independence, and overall satisfaction during inpatient hospitalization.